Cholinergic enzymes and inflammatory markers in rats infected by Sporothrix schenckii - Castro V.S.P. (2016)
© 2016 Elsevier Ltd.The aim of this study was to evaluate the cholinesterase activity in serum, whole blood, and lymphocytes, as well as to verify its relation to immune response in rats experimentally infected by Sporothrix schenckii. For this study, 63 Wistar rats (Rattus norvegicus), male, adult were divided into three groups: the negative control group (GC: n = 21), the group infected subcutaneously (GSC: n = 21), and the group infected intraperitoneally (GIP: n = 21). The groups were divided into subgroups and the following variables were evaluated at 15, 30, and 40 days post-infection (PI): acetylcholinesterase (AChE) activity in lymphocytes and whole blood, butyrylcholinesterase (BChE) activity in serum, cytokines levels (IL-1, IL-6, TNFα, and INF-γ), immunoglobulins levels (IgA, IgG, IgM, and IgE), and protein profile by electrophoresis. Both infected groups showed increased levels of inflammatory parameters (P < 0.05) in tissue and inflammatory infiltrates. The activities of AChE in lymphocytes and BChE in serum increased (P < 0.05) significantly in animals from the GSC group on day 40 PI compared to the GC group. Regarding the GIP, there was a marked increase in the AChE activity in lymphocytes on days 30 and 40 PI, and in whole blood on days 15, 30, and 40 PI compared to GC. Furthermore, IL-10, an anti-inflammatory cytokine, was also present in high levels during chronic systemic S. schenckii infections in animals. Therefore, it is concluded that cholinesterase has an important modulatory role in the immune response during granulomatous infection by S. schenckii.